PENGARUH SENAM AEROBIC LOW IMPACT TERHADAP KUALITAS TIDUR WANITA PREMENOPAUSE - Syarifah Haryanti; Susanti; Yenni Aryaneta; Admar Jas (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Insomnia is a symptom of premenopause. This is a result of the mental and physiological shifts that premenopausal women undergo. A decline in sleep quality, brought on by persistent sleep disruptions, might lessen one's standard of living. One non-pharmacological method for improving sleep quality is low-impact aerobic exercise. Finding out how premenopausal women responded to low-impact aerobic exercise for the quality of their sleep was the primary motivation for this study. This study used a pre- and post-test design, which is characteristic of quasi-experimental research. The Pittsburgh Sleep Quality Index (PSQI) was used to assess 30 premenopausal women. The effects of low impact aerobic exercise on the quality of sleep in premenopausal women was examined using data from the Wicoxon test, which had a Sig (2-tailed) value (P < 0.05). Final Product According to the study's findings,. With a p-value of 0.001 < 0.05, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, indicating a substantial change in the frequency distribution from the pre- to post-low impact aerobic exercise period. Results show that premenopausal women at their sleep quality after receiving low-impact aerobic exercise.